Insecticidal activities of Anethum graveolens L. and Illicium verum Hook. f. essential oils against Sitophilus zeamais Motschulsky - Chaubey, Mukesh K (Revista de Ciencias Agrícolas, 2021)
Inappropriate use of synthetic insecticides in pest management programs contribute in ozone depletion, neurotoxicity, carcinogenicity, teratogenicity, mutagenesis and resistance. These negative outcomes have diverted attention towards the use of plant products in insect’s population management. In this study, dill (Anethum graveolens) and star anise (Ilicium verum) essential oils were isolated by hydrodistillation method using clevenger apparatus, and evaluated for repellent, toxic and oviposition inhibitory potential against maize weevil Sitophilus zeamais (Coleoptera: Curculionidae) by fumigation and contact methods. In toxicity assay by fumigation method, median lethal concentrations (LC50) recorded were 0.316 and 0.243 μlcm-3 air; 0.362 and 0.284 μlcm-3; and 0.497 and 0.418 μlcm-3 of A. graveolens and I. verum oils and pure limonene after 24 and 48h exposure to S. zeamais adults, respectively. In contact toxicity assay, LC50 were 0.219 and 0.159 μlcm-2 area; 0.269 and 0.226 μlcm-2; and 0.567 and 0.386 μlcm-2 of A. graveolens and I. verum oils and pure limonene after 24 and 48 h exposure to S. zeamais adults, respectively. Both A. graveolens and I. verum oils and limonene reduced progeny production and acetylcholinesterase activity in S. zeamais adults when fumigated with sub-lethal concentrations. The outcomes of this study will help in preparation of essential oil based formulations for stored grain insect pest management.